2014
DOI: 10.1089/ars.2013.5229
|View full text |Cite
|
Sign up to set email alerts
|

Cancer PhototherapyviaSelective Photoinactivation of Respiratory Chain Oxidase to Trigger a Fatal Superoxide Anion Burst

Abstract: Aims: Here, we develop a novel cancer treatment modality using mitochondria-targeting, high-fluence, lowpower laser irradiation (HF-LPLI) in mouse tumor models and explore the mechanism of mitochondrial injury by HF-LPLI. Results: We demonstrated that the initial reaction after photon absorption was photosensitization of cytochrome c oxidase (COX), to inhibit enzymatic activity of COX in situ and cause respiratory chain superoxide anion (O 2 -) burst. We also found that HF-LPLI exerted its main tumor killing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 51 publications
3
61
0
2
Order By: Relevance
“…Several lines of evidence show that Cox acts as a photoacceptor and transducer of photosignals in the red and near-infrared regions of the light spectrum [28]. It seems that PBM increases the availability of electrons for the reduction of molecular oxygen in the catalytic center of Cox, increasing the mitochondrial membrane potential (MMP) and the levels of ATP, cAMP and ROS as well [29]. …”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence show that Cox acts as a photoacceptor and transducer of photosignals in the red and near-infrared regions of the light spectrum [28]. It seems that PBM increases the availability of electrons for the reduction of molecular oxygen in the catalytic center of Cox, increasing the mitochondrial membrane potential (MMP) and the levels of ATP, cAMP and ROS as well [29]. …”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…The evidence is based on the inactivation of caspase-8, activation of caspase-9 and by the release of cytochrome C. When this high dose is used, light inactivates Cox (instead of activating Cox), inducing a superoxide burst in the electron transport chain and, finally, produces oxidative damage against cancer cells [29]. Chu and co-workers already observed that PBM could induce a mitochondrial permeability pore transition when higher levels of ROS are produced.…”
Section: Molecular Mechanisms Of Pbmmentioning
confidence: 99%
“…All other conditions being equal, PSs that localize to mitochondria induce apoptotic cell death within a certain threshold of oxidative stress. Particularly with mitochondria, apoptotic cell death can ensue not only from oxidative damage induced by primary, photo-degenerated ROS, but also by superoxide anion generated as a secondary product due to photodamage of components of the electron transport chain [123]. In contrast, PSs targeting lysosomes either delay or block the apoptotic program, thus predisposing the cells to necrosis.…”
Section: The Mode Of Cell Deathmentioning
confidence: 99%
“…Several experimental aspects are detailed in each entry (see footnotes for more information). Each set of conditions has been obtained from a publication, with the particular reference provided in each case. Transition Biological model Light source Wavelength Power Spectral control 1 O 2 scavenging 1 O 2 enhancement Thermal control Reference 633 nm Human erythrocytesDye laser (pulsed)633 nm–YesNoNoNo[108]Human erythrocytesHe-Ne laser (cw)632.8 nm38–50 mWNopArpO 2 Yes[108]NC-37 lymphoblast lineHe-Ne laser (cw)633 nm1.2 mWNoNoNoNo[177]A2058 melanoma lineHe-Ne laser (cw)632.8 nm7 mWNoNoNoYes[178]Human skin fibroblastsHe-Ne laser (cw)632.8 nm18.8 mWYesNoNoYes[143]MCF-7 breast cancer lineHe-Ne laser (cw)632.8 nm14 mWNoNoNoNo[141]-A549Diode laser (cw)635 nm–No-SODNoNo[181]-EMT6-NAC-ASTC-a-1-EMT6 tumors in miceDiode laser (cw)635 nm–NoNoNoNo[181]-ASTC-a-1 tumors in mice-A549 adenocarcinomaLED (cw)637±17 nm–YesNoNoYes[146]-PtK2 renal line-U2OS osteosarcomaClinical trials in womenDiode laser (cw)…”
Section: Direct Optical Excitation Of 1o2mentioning
confidence: 99%